Impact of out-of-pocket expenses for surgical care on households in rural Haiti: a mixed-methods study - Padovany, Michelson MN; Patterson, Rolvix H; Bowder, Alexis N; O'Brien, Eva; Alkire, Blake C; Katz, Arlene M; Mitnick, Carole D; Lu, Chunling (BMJ open, 2022)
ObjectivesThis study aimed to report household catastrophic spending on surgery and the experiences of patients and families seeking surgical care in rural Haiti.DesignThe study used an explanatory, sequential mixed-methods approach. We collected both quantitative and qualitative data from the participants through interviews.SettingA rural tertiary hospital (St. Boniface Hospital) in southern Haiti.ParticipantsThere were 200 adult Haitian surgical patients who entered the study. Of these, 41 were excluded due to missing variables or health expenditure outliers. The final sample included 159 participants.Primary and secondary outcome measuresThe primary outcomes were (1) direct and indirect payments for surgical care; (2) the rate of catastrophic health expenditure (CHE) (as defined by the Sustainable Development Goals (10% of total household expenditure) and WHO (10%, 20%, 30% and 40% of household capacity to pay)) due to surgical care; and (3) common themes across the lived experiences of households of surgical patients seeking care.ResultsThe median household expenditure on surgery-related expenses was US$385.6, slightly more than half of per capita gross domestic product in Haiti (US$729.3). Up to 86% of households experienced CHE, as defined by the Sustainable Development Goals, due to receiving surgical care. Patients commonly paid for surgical costs through loans and donations (69.8%). The qualitative analysis revealed prominent themes related to barriers to care including the burden of initiating care-seeking, care-seeking journeys and social suffering.ConclusionsCHE is common for Haitian surgical patients, and the associated care-seeking experiences are often arduous. These findings suggest that low, flat fees in non-profit hospital settings may not be sufficient to mitigate the costs of surgical care or the resulting challenges that patients experience.